Pelaksanaan Bimbingan dan Konseling dari Perspektif Tindakan Sosial - Junaidi Junaidi; Neviyarni Neviyarni; Mudjiran Mudjiran; Herman Nirwana (Naradidik: Journal of Education and Pedagogy, 2022)
The behavior of school guidance counselors in providing their services is interesting to be studied from angles of sociological disciplines. An individual's behavior or actions have meaning for themselves and others. This study aimed to examine the actions of school guidance counselors in counseling activities based on the perspective of the social action concept. The research was library research. Precisely, it was a Systematic Literature Review (SLR). The SLR procedure follows the steps proposed by Francis and Baldesari. The process was conducted by collecting Guidance and Counseling articles from journals, proceedings, etc. The articles were limited based on the Guidance and Counseling program implementation criteria and suitability for the study focus. The study results revealed four types of actions that the school guidance counselors did in the counseling activities based on the perspective of the social action concept. First, based on the problem and cooperating factors, there was instrumental rational action. Second, based on belief or religious factors, there was value-oriented action. Third, based on empathy and comfort factors, there was affective action. Fourth, based on habit factors, there was traditional action.